2023
DOI: 10.1021/acs.jafc.3c00493
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Plant Polysaccharides as Antiaging Agents: Effects and Signaling Mechanisms

Abstract: Aging refers to the gradual physiological changes that occur in an organism after reaching adulthood, resulting in senescence and a decline in biological functions, ultimately leading to death. Epidemiological evidence shows that aging is a driving factor in the developing of various diseases, including cardiovascular diseases, neurodegenerative diseases, immune system disorders, cancer, and chronic low-grade inflammation. Natural plant polysaccharides have emerged as crucial food components in delaying the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…Polysaccharides are among the active ingredients crucial to maintain human health, which play an important role in the prevention and treatment of chronic diseases. 54,55 However, whether GEP has neuroprotective properties as a candidate for preventing and ameliorating PD has not been studied. Therefore, in this study, GEP was extracted, isolated, and identified, and then its effect and mechanism in the development of PD was explored.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides are among the active ingredients crucial to maintain human health, which play an important role in the prevention and treatment of chronic diseases. 54,55 However, whether GEP has neuroprotective properties as a candidate for preventing and ameliorating PD has not been studied. Therefore, in this study, GEP was extracted, isolated, and identified, and then its effect and mechanism in the development of PD was explored.…”
Section: Discussionmentioning
confidence: 99%
“…It can attach itself to the cell surfaces of surrounding algae, therefore stifling the growth of rival algae such as Skeletonema costatum [ 93 ]. Polysaccharides that exhibit allelopathic effects now clearly cling particularly to the target species’ cell surface, drastically restricting their proliferation and altering the number of certain species [ 94 ]. Moreover, the marine applications of these polysaccharides have shown considerable potential, such as in aquaculture to strengthen animal immune systems [ 95 ].…”
Section: Allelochemicals and Allelopathy Mechanisms In The Green Tide...mentioning
confidence: 99%
“…Both autophagy and mitophagy play a dual role in aging and aging-associated diseases. When they are weakened, they cause aging and agingrelated diseases; when they are too strong, they induce the autophagy death of normal cells [279,280].…”
Section: Autophagy Regulationmentioning
confidence: 99%